A Status Kelayakan Fortifikasi Vitamin A Minyak Goreng Sawit Tahun 2016 - 2020 di Wilayah Stunting - Yayu Sulistia; Dinalia Dinalia; Agustina Wanty Sumule; Annisa Dyah Lestari (Eruditio : Indonesia Journal of Food and Drug Safety, 2022)
Stunting still becomes a health problem that must be taken into serious consideration in Indonesia because it affects the quality of Human Resources in the future. Several attempts were made to meet the needs of micronutrients to overcome stunting. One of the Government's steps to decrease the stunting rate is adding more nutrients to foods often consumed by the public (fortification), one of which is palm cooking oil. Fortification of Vitamin A in palm cooking oil is a government program to decrease the rate of children lacking Vitamin A. This study aims to determine the feasibility status of vitamin A fortification in palm cooking oil that spreads within stunting areas in Central Sulawesi, South Sulawesi, North Sulawesi, and South Kalimantan. This research used a descriptive research method with a qualitative approach by using data collection from sipt.pom.go.id in the year 2016-2020. Samples were taken in districts where the stunting prevalence was located. Determining vitamin A levels using the Chromatography method based on SNI 7709:2019 with the standard vitamin A in cooking oil that spread in distribution channels was 20 IU/g. The status of Vitamin A fortification in palm cooking oil that spread in Central Sulawesi, South Sulawesi, North Sulawesi, and South Kalimantan was still below the standard, and if it was being averaged, for over the last five years, it has only reached 36.12%. Hence, it is suggested that the Government establish a specific regulation that regulates the use of safer palm cooking oil to maintain its quality, as well as the importance of education about the food stock storage for the public in the distribution area to maintain people's food stability